Tradisi nadran sebagai kearifan lokal masyarakat pesisir Cirebon dalam kaitannya dengan kelestarian lingkungan - Hadid, Mulyana; Surtikanti, Hertien Koosbandiah (Journal of Socio-Cultural Sustainability and Resilience, 2024)
Nadran is one of the annual traditions of the Cirebon coastal community. The life of coastal communities is identical to waters as a place for community livelihoods. All activities carried out including the organization of nadran related to the waters are things that ensure the economic sustainability of the community. Nadran is a form of expression of gratitude of the fishermen for the abundance of natural resources given by the Creator. Pelarungan as an important process in the nadran tradition and how it impacts the environment is the focus of this research. The research was conducted in Bondet River as one of the waters that flows directly into the Java Sea and is one of the places where nadran is held. Through observations, interviews, and questionnaires to the local community as well as literature studies, a qualitative descriptive analysis was carried out regarding the relationship between the nadran tradition in environmental conservation. There are 1 community leader and 15 questionnaire respondents consisting of community groups organizing the nadran tradition, observers and environmentalists, and ordinary people. Based on observations before and after the implementation of nadran, the condition of the Bondet River bank was observed to have garbage. The questionnaire showed that the community generally understands how to preserve the environment. The local community also organizes a cleaning schedule together. The results of the interview mentioned that the pelarungan process in the nadran tradition is actually a symbol for preserving nature. Full community support is needed regarding the sustainability of the nadran organization by applying the high value of local wisdom in the nadran tradition to ensure the environment remains sustainable. Public awareness, officers, and government supervision are important in preserving the nadran tradition while still paying attention to environmental sustainability.